Bioaktivitas Ekstrak Daun Tapakdara (Catharanthus roseus) terhadap Kadar Kreatinin dan Kadar Ureum Darah Tikus Putih (Rattus norvegicus) - Laksmi, Ni Luh Gede Merry Cintya; Dada, I Ketut Anom; Damriyasa, I Made (Buletin Veteriner Udayana, 2014)
The aim of the study was to evaluate the bioactivity of the Tapakdara leaf extract ( Catharanthus roseus ) on the creatinine and blood urea levels in rat ( Rattus norvegicus ). Tweenty four male rats (250-260 gram body weight) were devided into three goups, with 8 animals in each group. Group 1 as a control group that was geven placebo, the group 2 was treated with 100 mg/kg body weight of leaf extract orally and the group 3 was treated with 100 mg/kg body weight of leaf extract orally.   The animals were treated during 8 days after one week adaptation period. The examination of ceratinin and Blood Urea Nitrogen (BUN) were done in the last day of treatment. The result of the study indicated that the creatinin level of rats treated with 100 and 200 mg/kg BW was high significantly higher (p<0.01) than control group, however the creatinin level was in range of normal value. The level of Blood Urea Nitrogen of rats were treated with leaf extract of Tapakdara 100-200 mg/kg BW was significantly hihger (p<0.05) than control group, it was also in normal value.
Keywords: Catharanthus roseus, creatinin, Blood Urea Nitrogen (BUN), Rattus norvegicus